Sonographic findings in unilateral hydronephosis in a jaguarundi Puma yagouaroundi - case report - Oliveira, Hugo Salvador [UNESP] (2011)
A jaguarundi (Puma yagouaroundi) was sent to the diagnostic imaging sector for an abdominal ultrasound. In the present report, we observed a marked dilation of the left kidney, with anechogenic content and the presence of echogenic lines extending from the capsule towards the center of the kidney, sonographic evidence that indicates the diagnosis of hydronephrosis.